2012
DOI: 10.1100/2012/726948
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Secondhand Smoking to Mild Cognitive Impairment in Older Inpatients

Abstract: Up to now, controversy still exists regarding the role of secondhand smoking (SHS) in developing cognitive impairment. This study aimed to evaluate the prevalence of SHS in hospitalized older patients with cognitive deficit, particularly in those with mild cognitive impairment (MCI). Smoking history was classified into four groups: never smokers, former-active smokers/no SHS, active smokers, and secondhand smokers, and cognitive function into three levels: normal cognition (C), MCI, and dementia. A total of 93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…Previous studies have shown that passive smoking can increase the risk of cognitive impairment or dementia, which is a possible outcome of cognitive impairment [14][15][16]. The results of our study also provided evidence of the harmful effect of passive smoking exposure on cognitive function.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies have shown that passive smoking can increase the risk of cognitive impairment or dementia, which is a possible outcome of cognitive impairment [14][15][16]. The results of our study also provided evidence of the harmful effect of passive smoking exposure on cognitive function.…”
Section: Discussionsupporting
confidence: 77%
“…Nine papers were included in the final analysis, four of which reported research conducted in China (Chen, 2012 ; Chen et al , 2012 ; 2013a ; 2013b ), two in the UK (Llewellyn et al , 2009 ; Heffernan and O'Neill, 2013 ), two in the USA (Barnes et al , 2010 ; Akhtar et al , 2013 ), and one in Italy (Orsitto et al , 2012 ). They comprised seven cross-sectional studies, one between-groups design, and one longitudinal study.…”
Section: Resultsmentioning
confidence: 99%
“…All studies included standard cognitive tests and justified their use. Three studies also included clinical interview to verify diagnoses of dementia or the presence of cognitive impairment (Barnes et al , 2010 ; Chen, 2012 ; Orsitto et al , 2012 ). One paper included both a standardized test and self-reported functional limitation from memory impairment (Akhtar et al , 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations